To Calais, in ordinary time - Meek, James 1962- (Canongate, 2020)
"Three journeys. One road. England, 1348. A gentlewoman is fleeing an odious arranged marriage, a Scottish proctor is returning home to Avignon and a handsome young ploughman in search of adventure is on his way to volunteer with a company of archers. All come together on the road to Calais. Coming in their direction from across the Channel is the Black Death, the plague that will wipe out half of the population of Northern Europe. As the journey unfolds, overshadowed by the archers' past misdeeds and clerical warnings of the imminent end of the world, the wayfarers must confront the nature of their loves and desires."--Provided by publisher
Keywords: Upper class / England / Fiction; Clergy / England / Fiction; Agricultural laborers / Fiction; Voyages and travels / Fiction; Black Death / Fiction; France; Calais; Great Britain; Fiction; Historical fiction; History; Great Britain / History / Edward III, 1327-1377 / Fiction; Calais (France) / History / 14th century / Fiction